Boundary Layer Flow over a Moving Plate in a Nanofluid with Viscous Dissipation - Muhammad Khairul Anuar, Mohamed; Nor Aida Zuraimi, Md Noar; Mohd Zuki, Salleh; Anuar, Ishak (2014)
In this study, the numerical investigation of boundary layer flow over a moving plate in a nanofluid with viscous dissipation and constant wall temperature is considered. The governing equations for the model which is in non linear partial differential equations are first transformed to ordinary differential equations by using a similarity transformation. The ordinary differential equations are solved numerically by using the Kellerbox method. Numerical solutions are obtained for the reduced Nusselt number, Sherwood number and the skin friction coefficient as well as the concentration and temperature profiles. The features of the flow and heat transfer characteristics for various values of the Prandtl number, moving parameter, Brownian and thermopherosis motion parameters, Eckert number and Lewis number are analyzed and discussed.